Molecular and Serological Screening Support the Lack of Coxiella burnetii Circulation in Wild Birds of Portugal - Filipa Loureiro; João R. Mesquita; Luís Cardoso; Cristina Pintado; Sara Gomes-Gonçalves; Ana C. Matos; Vanessa Soeiro; Andreia Gonçalves; Filipe Silva; Manuela Matos; Ana Cláudia Coelho (Birds)
Coxiella burnetii is a highly infectious zoonotic pathogenic bacterium that has a major economic impact in the livestock industry throughout the world and causes unpredictable outbreaks in humans worldwide. Although it is known that birds are potential reservoirs of C. burnetii, their role in the epidemiological cycle of the pathogen has not been fully verified. Due to its non-specific symptoms and clinical signs, it is certainly an underdiagnosed disease. The objective of this study was to obtain more information on C. burnetii prevalence in wild birds in Portugal. Blood, plasma, and other tissue samples were obtained from wild birds admitted at wildlife rehabilitation centres in Portugal in the scope of passive surveillance. Antibodies specific to C. burnetii were screened using a commercial enzyme-linked immunosorbent assay according to the manufacturer’s instructions. Evidence of C. burnetii infection was sought based on the detection of bacterial DNA. No positive results were found, either in terms of antibodies to C. burnetii or molecular biology. These serological findings do not indicate the endemic circulation of C. burnetii in wild birds, which can be considered relevant information. However, a more complete and serialized approach over time is necessary to be able to make real inferences about the endemicity of the pathogen in the country and its dispersion among wild avian populations. qPCR results were also negative, a finding suggesting that this host population may not play a significant role in the transmission dynamics of C. burnetii. Given the importance of wild bird species as natural reservoirs of this zoonotic bacterium, we consider these data useful for multidisciplinary work in the prevention and control of Q fever, following a One Health approach.